La evolución jurídica del sistema matrimonial español desde la Constitución de 1978 a la admisión del matrimonio homosexual. - Fernández-coronado González, Ana (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2006)
The legal development of the Spanish marriage system, from its establishment in the Constitution of 1978 to the recent law of July 2005 on admission of marriage between persons of the same sex, has shown, in front of the doubts raised at the beginnings of the Spanish model, the “personalist” character of the marriage system. This «personalist» character has not only allowed the complete secularization of marriage, but also, as one of its direct consequences, the origin of a second generation of fundamental rights which takes root in the dignity of the person and its free development, whose most clear exponent is precisely the homosexual marriage.